Consequences appraisal on India’s opting out of the Regional Comprehensive Economic Partnership Agreement - L. N. Talalova; Chu Thanh Hang; A. V. Morozova (Вестник университета)
The political and economic context for India based on the results of the Regional Comprehensive Economic Partnership Agreement (RCEP) signed in November 2020 is considered. The benefits of strengthening economic cooperation for the participating countries from its signing are characterized. The hypothetical advantages for India in the case of its entry into RCEP are analyzed. In connection with country’s opting out of RCEP the authors have highlighted three segments of reasons for studying (political, legal and economic) that caused such India’s decision. Among the political reasons for India’s opting out of RCEP the problem of the Indo-Chinese border conflict over disputed territory escalating is emphasized. Among the legal reasons that determined opting out of the treaty, the issues of investment policy and intellectual property outside the World Trade Organization frameworks are noted. The economic reasons offset the benefits of RCEP for India are investigated. The connection between all three segments of causes is demonstrated. The experts’ forecasts is evaluated for India’s entry into third place in the world economy in terms of the gross domestic product contribution and the prerequisites for this are studied. It is concluded about the possibility of achieving the goal if a number of conditions are met and a set of necessary measures is carried out.